2009
DOI: 10.2144/000113220
|View full text |Cite
|
Sign up to set email alerts
|

Direct pH Measurements by using Subcellular Targeting of 5(and 6-) Carboxyseminaphthorhodafluor in Mammalian Cells

Abstract: As a means of reliably measuring intracellular pH, we have precisely targeted 5(and 6-) carboxyseminaphthorhodafluor to cellular subcompartments. This was accomplished by combining the well-established pH-sensitive dye with a protein-based reporter system. When expressed in cells, the reporter protein is designed to covalently bind ligands composed of a functional group and a reactive linker. In order to make a pH-sensitive ligand, we chemically coupled the pH sensor to a reactive linker. Several ligands of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Chemical tags have been used to study the localization and dynamics of proteins in living cells, especially in experiments that can not be easily performed with fluorescent proteins. In the last few years, chemical tags have been used to label proteins with fluorophores suited for advanced imaging technologies such as super-resolution (SR) microscopy [57][58][59], Ca 2þ -imaging [60][61][62], pH sensing [63], hydrogen peroxide detection [64], chromophore assisted light inactivation [36,65,66], and multi-photon microscopy [19]. Recently, Kosaka et al demonstrated the use of the Halo-tag to perform in vivo imaging studies in live animals for the first time [67].…”
Section: Applications Of Chemical Tags In Live Cell Imagingmentioning
confidence: 99%
“…Chemical tags have been used to study the localization and dynamics of proteins in living cells, especially in experiments that can not be easily performed with fluorescent proteins. In the last few years, chemical tags have been used to label proteins with fluorophores suited for advanced imaging technologies such as super-resolution (SR) microscopy [57][58][59], Ca 2þ -imaging [60][61][62], pH sensing [63], hydrogen peroxide detection [64], chromophore assisted light inactivation [36,65,66], and multi-photon microscopy [19]. Recently, Kosaka et al demonstrated the use of the Halo-tag to perform in vivo imaging studies in live animals for the first time [67].…”
Section: Applications Of Chemical Tags In Live Cell Imagingmentioning
confidence: 99%
“…The SNAP-tag technology has recently been applied to targeting sensors for Zn 2+ [63], Ca 2+ [64][65][66], and probes for hydrogen peroxide [67]. This strategy has also been applied to pH sensors that can be covalently linked to HaloTag [68]. A recent example for the nuclear localization of a highly sensitive BODIPY-based Ca 2+ -sensitive dye is shown in Figure 2b [66].…”
Section: Applications Of Tag-mediated Labeling Study Of Protein Functmentioning
confidence: 99%
“…Covalent linking of an environmentally sensitive dye to a protein of interest, allows local interrogation of the chemical environment, and selective activation of the dye in the proper environment. Targeting of pH sensors can be used to assess protein localization to acidic compartments such as endosomes[22], and targeting of lipid probes can be used to detect membrane associated proteins fluorogenically, as recently demonstrated with SNAP-tag directed Nile Red[23]. …”
Section: Introductionmentioning
confidence: 99%